1998
DOI: 10.1002/(sici)1099-0496(199803)25:3<167::aid-ppul6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophil cationic protein (ECP) and eosinophil protein X (EPX) in childhood asthma: The influence of atopy

Abstract: The purpose of this study was to determine the value of serum measurements of eosinophil cationic protein (ECP) and eosinophil protein X (EPX) in diagnosing asthma in children, and to investigate the influence of concomitant allergic diseases and atopic sensitization, assessed by skin prick tests (SPT), on these markers. ECP and EPX were determined in 36 children with asthma, in 33 children with other symptoms from lower airways disease (OSLA), and in 166 control children. Sixteen children with asthma but no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 30 publications
2
14
2
Order By: Relevance
“…EDN is likely to be generated and present at sites of inflammation associated with such disorders. EDN is present in the serum and nasal lavage fluid of healthy individuals at ∼20 ng/ml ( 58 , 59 ), but its concentration in the nasal lavage fluid of patients with allergic rhinitis can reach as high as 880 ng/ml ( 60 ), suggesting that EDN in tissues subject to allergic reaction or parasitic infection can reach a concentration (100∼1,000 ng/ml) necessary for the activation of DCs and enhancement of immune response described in the present study. Therefore, the capacity of EDN to activate DCs and to enhance a Th2-polarized immune response may provide a basis for the induction and/or maintenance of a Th2-polarized immune response during parasitic infection, allergy, or atopic reaction.…”
Section: Discussionmentioning
confidence: 51%
“…EDN is likely to be generated and present at sites of inflammation associated with such disorders. EDN is present in the serum and nasal lavage fluid of healthy individuals at ∼20 ng/ml ( 58 , 59 ), but its concentration in the nasal lavage fluid of patients with allergic rhinitis can reach as high as 880 ng/ml ( 60 ), suggesting that EDN in tissues subject to allergic reaction or parasitic infection can reach a concentration (100∼1,000 ng/ml) necessary for the activation of DCs and enhancement of immune response described in the present study. Therefore, the capacity of EDN to activate DCs and to enhance a Th2-polarized immune response may provide a basis for the induction and/or maintenance of a Th2-polarized immune response during parasitic infection, allergy, or atopic reaction.…”
Section: Discussionmentioning
confidence: 51%
“…Although the increase in serum ECP during the challenge was significant in infants with CMA and not in those with a negative challenge, the test did not discriminate between the challenge-positive and -negative infants at low cut-off values. However, the small number of high values (> 24.7 mg/L) [16] were mostly confined to the infants with CMA. Others have measured the postchallenge ECP earlier than we did in the present study [8,24].…”
Section: Discussionmentioning
confidence: 92%
“…CM-specific IgE were measured in 233 available single samples and serum ECP in 156 available paired samples by the Pharmacia CAP system (Pharmacia & Upjohn Diagnostics, Uppsala, Sweden). The following cut-off values were selected for serum ECP measured on challenge day 4: > 15 mg/L (suggested by the manufacturer) [14], > 20 mg/L [15] and > 24.7 mg/L [16].…”
Section: Serum Studiesmentioning
confidence: 99%
“…EPX encodes eosinophil peroxidase, a protein expressed by eosinophils. Previous investigations found that both serum and urine levels of EPX were elevated in children who had positive SPTs, as well as those with allergic diseases such as asthma, allergic rhinoconjunctivitis and atopic dermatitis [ 48 51 ]. A recent epigenome-wide study found multiple CpG sites, including one within PRG2 , which were associated with high versus low total IgE, primarily driven by eosinophils.…”
Section: Discussionmentioning
confidence: 99%